Gerakan Zero Waste: Implementasi Pengelolaan Sampah Plastik Melalui Pemilahan Sampah Rumah Tangga pada Masyarakat Puger Jember - Indahyani, Didin Erma; Rahayu, Prehatin Tri; Kusnadi; Negoro, Abdul Haris Suryo; Nurdiansyah, Yanuar; Wardani, L Dyah Purwita; Ganefo, Akhmad; Puspita, Indria Dwi; Sakinah, Wazirotus; Rudianto (Dental Agromedis, 2025)
The escalating problem of plastic waste has become a serious environmental concern, particularly in coastal areas such as Puger District, Jember Regency. This community service program aimed to implement a Zero Waste movement through household waste sorting as a fundamental step in community-based waste management. The methods applied included awareness campaigns and waste-sorting training and The results demonstrated a significant increase in public awareness and participation in waste sorting, as well as waste weighing to quantify the amount and types of household waste generated before and after the intervention. Moreover, there was a notable rise in family involvement in household waste management. This initiative proves that educational and participatory approaches can effectively drive behavioral change toward a low-waste lifestyle. The household-based Zero Waste movement offers a promising model for sustainable environmental empowerment in coastal communities.Keywords: zero waste, plastic waste, waste sorting, household, community empowerment, Puger-Jember